Combined adsorption process and photocatalytic degradation of some commercial herbicides over N-doped TiO2 particles supported on recyclable magnetic hexagonal mesoporous silica. Issue 11 (24th July 2019) - Hosseini, Navid; Toosi, Mohammad Reza
ABSTRACT: Magnetic hexagonal mesoporous silica (magnetic HMS) containing N-doped TiO2 was prepared by hydrothermal method and used for the removal of trifluralin, 2, 4-dichlorophenoxyacetic acid, and glyphosate herbicides at the presence and absence of UV/visible lights. The prepared samples were found as efficient for the removal of the herbicides and easily recyclable after treatment by UV irradiation. A red shift effect by nitrogen doping was also observed in the prepared samples resulting photocatalytic activity at the presence of visible light. Kinetic studies indicated that the photodegradation followed as the first order and k UV ≈ 10 k vis. The results also showed synergetic effects between the adsorption of herbicides on the surface of magnetic HMS and photoreactions over N-doped TiO2 species.